GAS CONCENTRATION MEASUREMENTS OF C2H2 USING A CALIBRATION RELATION OF TDLS SPECTROMETER - Mahmood, Ruaa Kahtan; Sekeb, Amani Ali; Deindee, Tabarek Falah; Al Masoudi, Amal Abd Al-Amir (Prodi Fisika FST UNJA, 2025)
The work has been demonstrated by varying the wavelength of a tunable DFB laser diode, a Tunable Diode Laser Spectroscopy (TDLS) simulation method employing a sinusoidal signal to enhances the sensitivity of the spectrometer. Since the laser drive current is tuned, altering the current will cause the laser diode's wavelength to shift within the Near Infrared (NIR) tuning range of around 0.02 nm. A set focus value of 0.5 ppm and a fixed open path length (distance between laser source and back reflector) of 100 m were used to evaluate the TDLS's sensitivity. A MATLAB code was written to change the exact wavelength of the near infrared region, and the frequency domain evaluations were taken to extract the value of the second harmonic, which is an indication of the presence of the gas to be detected. The value of wavelength has been found in NIR region of the acetylene was about 1530. 47 nm. It should be noted the amount of gas concentrations were performed at a distance of 100 meters, with the gas concentration being N = 0.05 to 0.5 ppm in 0.2 increments.